Integrating the Concept of Qur’anic Geography into Sustainable Development Strategies: A Thematic Analysis of Food Security - Ery Sunandar (ZAD Al-Mufassirin, 2026)
Food security in Indonesia is strained by the degradation of 8.2 million hectares of agricultural land and a declining farmer regeneration rate. This study analyzes the intersection between geographic spatial instruments and Qur'anic thematic principles to formulate a more measurable sustainable development framework. Using a qualitative-interdisciplinary method, this research synthesizes spatial-ecological data with tafsir maudhu’i focused on resource management verses. The results establish a "Teo-Ecological Framework" for food security consisting of three primary indicators: (1) Al-Mizan-based Spatial Planning, which utilizes land carrying capacity as the treshold for industrial expansion; (2) Khalifah-oriented Resource Stewardship, a model for precision agriculture that integrates theIoT (Internet of Things)  with ethical resource use; and (3) Zero-Israf Logistics, a supply chain management indicator to reduce national food loss and waste. This study concludes that the integration of these Qur'anic geographic values into Regional Spatial Planning (RTRW) provides a concrete ethical-technical basis for long-term food resilience, moving beyond purely production-centric policies.